2003
DOI: 10.1093/jn/133.11.3386
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine-N-methyltransferase Activity and Dietary Choline Regulate Liver-Plasma Lipid Flux and Essential Fatty Acid Metabolism in Mice

Abstract: Phosphatidylethanolamine-N-methyltransferase (PEMT) catalyzes the methylation of phosphatidylethanolamine to form phosphatidylcholine (PC) and represents one of the two major pathways for PC biosynthesis. Mice with a homozygous disruption of the PEMT gene are dependent on the 1,2-diacylglycerol cholinephosphotransferase (CDP-choline) pathway for the synthesis of PC and develop severe liver steatosis when fed a diet deficient in choline. The present study used quantitative lipid metabolite profiling to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 21 publications
4
120
0
1
Order By: Relevance
“…In the liver, the conversion of phospholipid from PE to PC (via SAMe and PEMT) is critical for DHA mobilization from the liver into the plasma (Figure 2). When this reaction does not occur normally, as seen in PEMT knockout mice (and possibly in folate deficiency), plasma concentrations of DHA are selectively decreased (Watkins et al, 2003). Since heavy alcohol intake may cause SAMe depletion in the liver (Lieber, 2000), folate availability may be especially critical for the creation of PC from PE in subjects who drink alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, the conversion of phospholipid from PE to PC (via SAMe and PEMT) is critical for DHA mobilization from the liver into the plasma (Figure 2). When this reaction does not occur normally, as seen in PEMT knockout mice (and possibly in folate deficiency), plasma concentrations of DHA are selectively decreased (Watkins et al, 2003). Since heavy alcohol intake may cause SAMe depletion in the liver (Lieber, 2000), folate availability may be especially critical for the creation of PC from PE in subjects who drink alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in PEMT-deficient mice has revealed promising results for benefits of choline supplementation. Namely, PEMTdeficient mice develop severe steatosis with both a cholinedeficient diet and a regular chow diet [35]. However, levels of liver TGs significantly decrease when these mice are supplemented with choline.…”
Section: Animal Studiesmentioning
confidence: 99%
“…However, regulation of CT activity has also been implicated in many other biological processes, including neurite growth (50), neural tube closure (51), and fetal development (52). It has also been suggested that dysregulation of hepatic PC biosynthesis disrupts the distribution of long chain polyunsaturated fatty acids in liver and plasma (53).…”
Section: Figmentioning
confidence: 99%